There is no place like work: Evidence on health and labor market behavior from changing weather conditions - Adrian Chadi (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2017)
Ill-health is commonly believed to be detrimental for labor market outcomes. Yet, causal evidence mostly comes from analyses of severe shocks, whereas minor variations in health are not only more common but also a better target for prevention measures. This study makes use of data from the German Socio-Economic Panel merged with data on regional weather conditions prior to the date of a survey interview. Weather conditions are capable of affecting peoples' health. While bad weather leads to minor reductions in health, the effect on working hours is, surprisingly, positive. Comprehensive survey data on time-use and subjective assessments of people's working lives allows discussing the mechanisms behind these findings, such as whether the weather manipulates people's allocation of working time and leisure. The evidence seems to support the idea that less healthy individuals compensate the potential impairments on labor productivity by spending some additional time at the workplace. Analyzing effect heterogeneity across subgroups, the study shows that there is only little variation across industries, but stronger increases in working time among people in part-time jobs. While there are no gender-specifics in the health impairments due to bad weather, the increase in working hours is driven by women.
Keywords: I12; J22; Q50; 330; quasi-experiment; weather; health; labor supply; SOEP; gender differences